Differential inhibitory action of cotton root juices on isolates of Fusarium oxysporum f. sp. vasinfectum (Atkinson) Snyder and Hansen - Khan, I.D.; Sabet, K.A. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
The effect of sterile root juices from Karnak and Menoufi cotton vines (Gossypium barbadense L.) was examined for any inhibitory principle against four strains (FFFF) of Fusarium oxysporum f. sp. vasinfectum (Atkinson) Snyder & Hansen, the causal organism of cotton wilt in Egypt. The growth of Fra was not affected by root juices of 'Karnak' and 'Menoufi' at undiluted concentrations. The germs of the strains were found to be differentially inhibited. An interesting point revealed was that in the spore germination technique, a low percent inhibition of Fre was observed by 'Menoufi's juice. To explain this situation, pathogenicity assays were conducted and it was noticed that under certain conditions the cotton plant can not only be infected by the strains but can also show typical mosaic symptoms on the leaves. 'Menoufi's infection was obtained only when the pathogenicity experiments were carried out at "maximum stringency" and "effective inoculum potential" of the pathogen in unsterilized Nile silt. On the basis of the data obtained, it has been shown that in Egyptian cotton varieties there is an inverse relationship between the amount of inhibition (of the strains tested) and the disease potential achieved in the variety.